Evaluation of stress cracking on geomembranes after accelerated tests (2014)
This paper presents results of stress cracking tests performed in high density polyethylene (HDPE) geomembranes (GM). Stress cracking tests were performed in accordance to ASTM D5397: Notched Constant Tensile Load Test (NCTL) and Single Point- Notched Constant Tensile Load Test (SP-NCTL). Tests were conducted to the fresh sample at 50ºC (standard test) and at 70ºC (accelerated condition) in order to compare the SC values. Results from accelerated tests (NCTL) showed, for instance, a total economy of 390 hours (comparing load stages of 25% yield stress) to perform the tests.